Use of Modified Semantic Differentials To Evaluate Formal Organizational Structure - Hay, Robert D. (Academy of Management Journal, 1969)
A modified semantic differential is a valuable instrument for getting qualitative evaluations in numerical form. It can be used to measure attitudes about certain aspects of formal organization structure such as span of supervision and shared authority plus other applications.